A real-time medical cartography of epidemic disease (Nodding syndrome) using village-based lay mHealth reporters - Valdes Angues, Raquel; Suits, Austen; Palmer, Valerie S.; Okot, Caesar; Okot, Robert A.; Atonywalo, Concy; Gazda, Suzanne K.; Kitara, David L.; Lantum, Moka; Spencer, Peter S. (PLOS Neglected Tropical Diseases, 2018)
Author summary Absence of health monitoring of rural populations in low-income countries allows diseases to emerge and spread for months before their detection by public health authorities. We tested the feasibility of using smartphones operated by lay villagers to report health information in real time from the populations in which they reside. Eight young lay adults from remote rural regions of northern Uganda were trained to administer questions and transmit answers using pre-programmed mobile phones. Weekly, over a 3-month period, each lay reporter monitored an average of 40 children suffering from an epileptic disorder known as Nodding syndrome (NS). For each child, episodes of head nodding, convulsions, injuries, deaths and availability of anti-seizure medication were reported weekly and the data instantaneously assembled by customized software for analysis in Uganda and the USA. This system not only provided a real-time map of the health status of children with established NS but also discovered children previously unknown to have head nodding. While logistical hurdles had to be overcome, the study demonstrates the feasibility of using lay workers operating software-equipped mobile smartphones to build a current and continuously updatable medical geography of the rural populations in which they reside. Wide application of such systems could result in the early detection and control of disease.